Democracia de proprietários, prédistribuição, e rendimento básico incondicional - Merrill, Nathaniel Roberto Buil (2017)
In this article I begin by exposing the theme of property-owning democracy, from John Rawls to its republican beginnings, examining its theoretical foundations and its institutional implications. I then argue that a property-owning democracy can be justified as a form of pre-distributive justice. Finally, I advocate unconditional basic income as an example of a desirable pre-distributive public policy in a property-owning democracy.